STRATEGI PENGEMBANGAN PENGOLAHAN AYAM POTONG DI PT. MALINDO FEEDMILL - Widodo, Tulus; Utomo, M.Si., Dr. Ir. Tanto Pratondo; Suroso, Erdi; Hidayati, Sri; Sartika, Dewi; Widaputri, Silaturahmi (Jurusan Teknologi Hasil Pertanian, 2024)
Local food-based agro-industry requires raw materials in the form of agricultural products that are suitable for processing into food products. The need for meat production as a source of animal protein for the community is increasing. This can be seen from the demand for chicken meat which is increasing every day. The high demand for chicken makes several meat business actors carry out slaughtering both in slaughterhouses and slaughterhouses. PT Malindo Feedmill is a company engaged in the animal feed industry, chick farming and broiler farming as well as processed food. Several aspects are needed to develop agro-industry at PT Malindo Feedmill so that the company can innovate for the future and can generate large revenues. In this case, it is necessary to analyze what businesses and strategies are applied for the development of agro-industry at PT Malindo Feedmill. Data analysis using the survey method and continued with SWOT analysis. The results of the SWOT analysis show that the establishment of a Chicken Slaughterhouse for the company is feasible for the company to establish, this is because the score of strengths and threats is 1.35 and opportunities and threats have a score of 2.19 which means that the chicken slaughterhouse development strategy is in quadrant 1 where the company has strengths and opportunities in running a business.